2021
DOI: 10.1039/d1gc01429c
|View full text |Cite
|
Sign up to set email alerts
|

A catalytic approach via retro-aldol condensation of glucose to furanic compounds

Abstract: The synthesis of new type furan-based compounds other than 5-hydroxymethylfurfural from glucose is a very attractive yet underexploited strategy. We report here a catalytic conversion of glucose with acetylacetone (acac)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Due to the instability of glycolaldehyde under reaction conditions and the rapid dehydration properties of NAE (NAG conversion into 3AF is complete within 20 min), it is difficult to directly detect these intermediates. Inspired by a recent study conducted by Repo, [38] we sought to trap the intermediate glycolaldehyde in situ with acetylacetone to obtain the corresponding furan 2‐methyl‐3‐acetylfuran (MAF). Satisfyingly, MAF was detected under the Ba(OH) 2 reaction conditions (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the instability of glycolaldehyde under reaction conditions and the rapid dehydration properties of NAE (NAG conversion into 3AF is complete within 20 min), it is difficult to directly detect these intermediates. Inspired by a recent study conducted by Repo, [38] we sought to trap the intermediate glycolaldehyde in situ with acetylacetone to obtain the corresponding furan 2‐methyl‐3‐acetylfuran (MAF). Satisfyingly, MAF was detected under the Ba(OH) 2 reaction conditions (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…To mechanistically study the NAG transformation into 3AF, acetylacetone was used as a trapping agent in situ to gain the corresponding products based on the method reported by Repo and co‐workers [38] . The NAG catalyzed by Ba(OH) 2 −H 3 BO 3 −NaCl or H 2 MoO 4 were conducted at 180 °C for 20 min in DMF/acetylacetone or H 2 O/acetylacetone.…”
Section: Methodsmentioning
confidence: 99%
“…It has been known that converting glucose to TriEE takes a few steps as shown in Scheme 2. 12,29 First, glucose undergoes a [2 + 4] retro-aldol condensation reaction to form GA and erythrose, and the latter could further go through a [2 + 2] retroaldol condensation reaction to generate two molecules of GA. 30 GA takes part in the acetalization reaction with ethanol and forms hemiacetal (1-ethoxyethane-1,2-diol) and GDEA. Brønsted acids are acknowledged as effective catalysts for the hemiacetalization and acetalization reactions.…”
Section: Catalyst Sievingmentioning
confidence: 99%
“…Recently, we reported the synthesis of substituted furanic compounds with good yields from glucose and acetylacetone (acac) via a cascade type retro-aldol condensation and GG reaction. 45 Acac is seen as a sustainable component in the reaction as it is available from glucose via chemical transformation or biosynthetic routes. 46,47 During the continuing research course, we observed a new type of bisfuranic compound obtained from xylose.…”
Section: Introductionmentioning
confidence: 99%